Influence of the supramolecular arrangement in the electrical conductivity of poly(thiophene) thin films - Braunger, Maria L. [UNESP]; Alessio, Priscila [UNESP]; Furini, Leonardo N. [UNESP]; Constantino, Carlos J. L. [UNESP]; Olivati, Clarissa A. [UNESP] (American Scientific Publishers, 2017)
Thin films of regioregular polythiophene derivatives have had their optical, structural and morphological properties characterized, but there is still a lack of comparative studies to determine the effect from deposition techniques, especially on the electrical properties. In this study, we produced Langmuir-Schaefer and spin-coated films of regioregular alkyl-substituted polythiophene derivatives (P3AT) to investigate how distinct supramolecular arrangements can affect their properties. The Langmuir-Schaefer films deposited on indium-tin oxide substrates were observed to grow linearly with the number of layers, according to UV-visible absorption spectroscopy. Atomic force microscopy and Brewster angle microscopy were carried out for morphological characterization. From electrical transport measurements, the DC electrical conductivity of Langmuir-Schaefer films of P3AT was higher than the corresponding spin-coated films, which can be related to the dissimilar roughness and molecular-level organization provided by the Langmuir-Schaefer technique.
Keywords: Electrical conductivity; Langmuir-Schaefer; Polythiophene